Enhanced Viability and Anti-rotavirus Effect of Bifidobacterium longum and Lactobacillus plantarum in Combination With Chlorella sorokiniana in a Dairy Product - Cantú-Bernal, Servando; Domínguez-Gámez, Maribel; Medina-Peraza, Ivana; Aros-Uzarraga, Elizama; Ontiveros, Noé; Flores-Mendoza, Lilian; Gomez-Flores, Ricardo; Tamez-Guerra, Patricia; González-Ochoa, Guadalupe (Frontiers in Microbiology, 2020)
Microalgae and probiotics such as Bifidobacterium and Lactobacillus genera are associated with human beneficial effects. The aim of this study was to evaluate the prebiotic activity of Chlorella sorokiniana in Bifidobacterium longum and Lactobacillus plantarum viability incorporated into a dairy product (flan) and study its antiviral effect against rotavirus, which is one of the major diarrhea-causing pathogens worldwide. Microalge were isolated from a Mexican river and characterized by molecular tools. Their prebiotic activity was evaluted determining Bifidobacterium longum and Lactobacillus plantarum shelf-life after incorparation into the food matrix. In addition, HT-29 cells were infected with rotavirus Wa and treated with of L. plantarum and B. longum (1 × 109 CFU/mL each) metabolites alone or in combination with Chlorella sorokiniana (1 × 109 cells/mL); viral titers in probiotics and/or microalgae-treated cells were evaluated for antiviral activity. Results indicated that incorporation of C. sorokiniana into a dairy product not only significantly (p < 0.05) improved L. plantarum and B. longum viability, but also increased their antiviral activity. Furthermore, C. sorokiniana was observed to possess potent anti-rotavirus effect. Although more studies are needed, the results suggest that the incorporation of this microalga into a dairy product confers prebiotic and antiviral effects, which indicate that C. sorokiniana might be used as an ingredient to design products with additional health benefits. To our knowledge, this is the first report of C. sorokiniana characterization as a prebiotic and antiviral agent.